260‐GHz differential amplifier in SiGe heterojunction bipolar transistor technology. Issue 3 (1st February 2017) - Yoon, D.; Seo, M.‐G.; Song, K.; Kaynak, M.; Tillack, B.; Rieh, J.‐S.
Abstract : A 260‐GHz amplifier in a SiGe heterojunction bipolar transistor (HBT) technology is reported. It is based on three‐stage differential cascode topology and adopts a passive shunt transistor pair at the output of each amplifying stage to relax instability caused by parasitic base inductance of amplifying transistor pair. The instability of the amplifier can be mitigated by tuning the base bias voltage of the shunt transistor pair. Peak gain of the amplifier was measured as 15 dB at 260 GHz. DC power dissipation is 112 mW. The chip occupies 300 × 160 μm 2 excluding Baluns and probing pads.